Thermoplastic material selection : a practical guide - Larson, Eric R.; ScienceDirect eBooks (Amsterdam : William Andrew is an imprint of Elsevier, 2015)
Thermoplastic Material Selection: A Practical Guide presents current information on how proper material selection is a critical component of any manufactured product. The text is a practical guide to a difficult process, giving the reader a fundamental grounding in thermoplastic materials and providing the tools they need to save time, money, and frustration. The book provides an overview of the most commonly used thermoplastic materials, including discussions of the different chemical families, plastics categories, and material grades - and the implications of these differences on the material selection process. It provides fresh insights on the traditional methods of material selection based on performance and cost, and also discusses the use of non-traditional methods based on subjective evaluation. Subsequent sections include references on tools that can be used to conduct further exploration, how to accurately select the most suitable material, writing an effective material specification, and working with material suppliers and distributors.
Online resource; title from PDF title page (Ebsco, viewed May 11, 2015).
Includes bibliographical references and index.
Elsevier
Keywords: Thermoplastics -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Thermoplastics; Electronic books